2021
DOI: 10.3389/fmicb.2021.744075
|View full text |Cite
|
Sign up to set email alerts
|

Top-Down Enrichment Strategy to Co-cultivate Lactic Acid and Lignocellulolytic Bacteria From the Megathyrsus maximus Phyllosphere

Abstract: Traditionally, starting inoculants have been applied to improve ensiling of forage used for livestock feed. Here, we aimed to build up a bioinoculant composed of lactic acid-producing and lignocellulolytic bacteria (LB) derived from the Megathyrsus maximus (guinea grass) phyllosphere. For this, the dilution-to-stimulation approach was used, including a sequential modification of the starting culture medium [Man, Rogosa, and Sharpe (MRS) broth] by addition of plant biomass (PB) and elimination of labile carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 75 publications
(107 reference statements)
0
4
0
Order By: Relevance
“…Polymer‐degrading Pseudomonadales were the most dominant species. The bottom layer was primarily colonized by Lactobacillales , which exhibited the potential to biodegrade plastics, [ 55 , 56 ] and Hydra vulgaris , which produced a cellulolytic enzyme. [ 57 ] Cellulolytic enzymes are composed of a variety of complex enzyme systems, which can break the glycosidic bond and gradually hydrolyze macromolecular cellulose into glucose.…”
Section: Resultsmentioning
confidence: 99%
“…Polymer‐degrading Pseudomonadales were the most dominant species. The bottom layer was primarily colonized by Lactobacillales , which exhibited the potential to biodegrade plastics, [ 55 , 56 ] and Hydra vulgaris , which produced a cellulolytic enzyme. [ 57 ] Cellulolytic enzymes are composed of a variety of complex enzyme systems, which can break the glycosidic bond and gradually hydrolyze macromolecular cellulose into glucose.…”
Section: Resultsmentioning
confidence: 99%
“…An innovative top-down strategy is developed by co-cultivation of LAB (Lactic acid bacteria) and LB (lignocellulolytic bacteria) populations by using a sequential and rational modification of MRS broth by overall dilution to stimulation approach ( Díaz-García et al, 2021a ). In this strategy, it is very important to manipulate the whole microbial consortium to obtain the desired function.…”
Section: Strategies For the Selection Of Consortium Membersmentioning
confidence: 99%
“…Recently, the degradation of PBAT by a marine microbial consortium showed that synergism and division of labor could be key mechanisms ( 86 ), similar to what is reported for lignin catabolism ( 87 ). Thus, the use of microcosms or enrichment liquid cultures could be excellent “top-down” strategies to select plastic-degrading microbial consortia (PDC) from environmental microbiomes ( 88 ). A proposed strategy to select PDC is the “dilution-to-stimulation” approach ( 89 ), where plastics (or their derived monomers) are used by the microbes as the sole carbon source.…”
Section: Correlation Between Plastic Biodegradation Lignocellulose An...mentioning
confidence: 99%